Influence of strata characteristics on face support requirement for roof control in longwall workings - A case study - Singh G.S.P.; Singh U.K. (My University, 2025)
A proper understanding of the influence of strata characteristics on progressive caving behavior and support performance is essential for reliable planning, rational support selection and safe operation of longwall faces. This paper reports numerical modelling results to explain the influence of roof characteristics on strata behaviour and adequacy of support during face advance in three different conditions. The study reveals that although the field support of a given capacity was adequate to work bottom section under general roof formation, it needed to be used in conjunction with a rapid yield valve (RYV) having a peak discharge capacity of 470 L min21 and a response time of 52 ms for safe extraction of top section working. A safe and smooth extraction of the bottom section longwall panels under hard roof formation required higher capacity support in conjunction with an RYV for safe management of en masse caving under prevailing strata conditions. © 2012 Institute of Materials, Minerals and Mining.